P53 mRNA in- Situ Hybridization analysis and Immunohistochemical Expression in Lung Cancer: A Comparative Study. - Abdul-Majeed, Ban A. (Journal of the Faculty of Medicine Baghdad, 2010)
Background and objectives: P53 gene mutation and deletion are among the important molecular markers linked to lung cancer. In most cases, the inactivating mutations affecting both p53 alleles are acquired in somatic cells. Less commonly, the mutations are inherited ones. The aim of the present study was to analyze the frequency of having a wild and/or a mutated p53 gene in lung cancer compared to benign lung lesions and to relate these findings to different morphological types and grades of lung cancer.Patients, materials and methods: In this retrospective study, the histopathology blocks of 30 lung cancer cases covering the period from2002 to 2007were obtained from the archives of the histopathology section of the Special Surgeries Hospital Laboratories. Twenty cases of non-malignant lung diseases served as a control group. Sections made on charged slides were subjected to p53 mRNA in-situ hybridization and p53 protein immunohistochemical staining.Results: Positive p53 in situ hybridization signal was detected in 29 cases of carcinoma. The highest percentage score was score- 3 being detected in 16(53.3%) cases. High intensity of hybridization signal was seen in 17(56.7%) cases. All control cases revealed positive hybridization signals (100%). Seven cases revealed score-3 and of these 5 revealed high intensity of hybridization. Immunohistochemical expression of p53 protein was seen in 21(70%) cases of carcinoma with score-3 being found in 11(36.7%) cases, 7cases revealed score-3 in situ hybridization signals as well. High intensity was found in 11(36.7%) cases, 10 of them showed high intensity of hybridization signal. Only two control cases (10%) revealed positive p53 expression. They showed score-2 and low intensity of expression. Significant statistical correlations were found between in situ hybridization signaling and immunohistochemical expression scores and intensities in carcinoma cases with p value < 0.05.Conclusion: The relations of tumor grade to the score and intensity of ISH signaling and IHC expression were significant suggesting the importance of having higher scores and intensities of positive cells which is an indication of tumor progression and prognosis. Studying p53 gene integrity or expression of a mutated protein is important for predicting tumor prognosis and establishing a proper therapeutic approach.